Factory economics: economic efficiency and its conditions as a foundation for production system management - Noal, Lúcio Cantarelli (Universidade do Vale do Rio dos Sinos, 2025)
Enhancing efficiency and productivity in organizations is a fundamental necessity to which we are inextricably linked. While technical efficiency has been widely studied, research on economic efficiency remains relatively scarce in comparison. Methodologies such as Lean primarily focus on optimizing technical efficiency in manufacturing systems. However, while technical improvements are undeniably important, it is crucial to recognize that gains in technical efficiency do not always translate proportionally into gains in economic efficiency. This study argues that understanding the production system from an economic perspective is essential for effectively applying concepts, methods, techniques, and tools in manufacturing systems. To explore this, an design science research (DSR) was conducted, beginning with problem identification and the establishment of a theoretical framework, followed by the implementation of the intervention and an evaluation of its effects. The theoretical framework was developed through a systematic literature review (SLR), examining the relationship between Lean and efficiency in both manufacturing and service systems. The intervention aimed to compare the application of Lean principles and the Theory of Constraints (TOC) in synchronizing production within an automotive assembly line. The economic results revealed that TOC synchronization was more effective than the Lean approach, reducing total costs by 29.9%. In a subsequent longitudinal analysis through a case study, TOC implementation led to a 66.9% increase in economic efficiency. These findings underscore the pressing need for further research on economic efficiency in manufacturing systems. The primary limitation of this study is that the research was conducted on a single case and was not applied across multiple manufacturing systems.
Keywords: Lean; Teoria das Restrições (TOC); Drum-Buffer-Rope (DBR); Eficiência econômica; Theory of Constraints (TOC); Economic efficiency; ACCNPQ::Engenharias::Engenharia de Produção